Exploring Teachers’ Strategies in Strengthening Reading and Writing Literacy to Enhance Students’ Creative Writing Skills at Madrasah Ibtidaiyah - Tri Astuti, Efi; M.Fahmi Maulana; Siti Rohmah (UIN Sunan Kalijaga Yogyakarta, 2025)
Literacy plays a pivotal role in shaping students’ intellectual, moral, and creative capacities, especially within Islamic elementary education. However, many students in Indonesia still struggle to connect reading and writing literacy with creative expression. This study explores teachers’ strategies in strengthening reading and writing literacy to enhance students’ creative writing skills at Madrasah Ibtidaiyah Negeri (MIN) 4 Demak. Using a qualitative field research design involving observations, interviews, and documentation, the findings reveal that literacy programs at MIN 4 Demak are implemented holistically, that is, integrated across daily routines, classroom instruction, and extracurricular activities. These include morning reading habituation (Gerakan Literasi Madrasah), guided writing sessions, Qur’an-based reflection journals, and creative literacy events such as “Literacy Fridays” and “Writing Corners.” Teachers function as facilitators by modeling expressive reading, scaffolding students’ ideas during brainstorming, and guiding them to express Islamic moral values through stories, poems, and reflective essays. Through these activities, students not only develop linguistic and creative abilities but also strengthen their moral awareness and self-confidence. The results suggest that integrating literacy practices with Islamic educational values fosters a sustainable literacy culture one that nurtures creativity, critical thinking, and character development among elementary students.